PSYCHO-SOCIAL IMPACT AND QUALITY OF LIFE AMONG PATIENTS WITH PSORIASIS ATTENDING A TERTIARY CARE INSTITUTE IN NORTH CHENNAI - Khan, Aadam Ahmed; T, Aathi Raja; P, P Seenivasan; T, Susila (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To assess the psycho-social impact of psoriasis and the quality of life (QoL) among psoriasis patients. Methods: This is a cross-sectional study with a sample size of 140 done in a dermatology outpatient clinic in a tertiary care institution in North Chennai. The dermatology life quality index (DLQI) was the primary tool for assessing QoL. Results: The study participants’ mean±SD DLQI score was 8.84±4.59. Out of 140 patients, 32.9% had severely affected QoL with a DLQI score >10. About 81.4% of study participants felt embarrassed due to their skin lesions, and marital life was affected by 36.4%. Suicidal thoughts and alcohol addiction (for coping up) were found to be prevalent among 12.9% of the subjects, both of which were maladaptive coping strategies. It was found that patients with DLQI scores of 10 or more tend to cling to alcohol as a coping mechanism, and this association is statistically significant. Further, a significant association was also noted between the site of the lesion and marital life getting affected by psoriasis. (x2=9.893, p=0.042). Conclusion: Patients with psoriasis are subjected to an intricate web of physical and psycho-emotional challenges. Hence, the physician offering chronic follow-up care to those patients needs to adopt a holistic strategy to address their continuing medical and psychosocial needs.